Ecological Communication about Ecological Issues: A Field Experiment on Extended Producer Responsibility - Paulína Jalakšová; Stella Košíková; Richard Priesol; Berenika Tužilová (Ekonomický Časopis)
Extended Producer Responsibility (EPR) is a public policy that holds producers accountable for the post-consumer stage of their products. In Slovakia, producers are required to register in the national producer registry and pay the corresponding fees. However, a significant number of producers – particularly those dealing with packaging and non-packaging products – fail to comply, effectively becoming free riders. To compare the effectiveness of electronic versus paper-based communication, we sent registration and payment reminders to over 3,000 firms. Among companies established in the previous year, there was no significant difference in registration rates between the two types of communication. However, for longer-established firms, paper-based reminders proved more effective when the message consisted only of a general reminder. This difference disappeared when the reminder included a threat of penalty, suggesting that electronic and paper-based messages were equally effective in that context.